AI automation is enclosure: the case for data rent modelled on ground rent - Jai Vipra (European Law Open)
Taking the claims of Artificial Intelligence firms seriously implies that these firms now benefit from legal defaults and vacuums that allow them to enclose economically relevant intellectual capacity and therefore cause mass displacement of labour. This process is carried out unilaterally and without compensation, and thus likely results in the pauperisation of a significant proportion of people worldwide. Thomas Paine’s analysis of land enclosures provides one way to think of enclosures of economically relevant intellectual capacity, and points to a universal basic income drawing from a data tax as a right derived from this enclosure.